Giant Right Atrial Abscess in a Premature Infant With Fungal Endocarditis in a Developing Country. Issue 5 (September 2020) - Pradegan, Nicola; Muñoz, Ysailis Mariñez; Reyes, Marcos; Toribio, Janet; Herrera, Cesar J.; Leon-Wyss, Juan R.
Although infective endocarditis rarely appears during infancy, fungal infections remain a concern in the preterm neonatal population as the result of compromised immunity, prolonged hospitalization, and invasive procedures. The increased awareness of fungal colonization and improvements in medical therapy have not reduced the high mortality rate of mycotic infections in premature newborns, especially in developing countries, and there is no consensus on the surgical timing to treat neonatal fungal endocarditis. We present the case of a two-month-old boy with a history of three weeks of hospitalization for prematurity. After being discharged, the patient developed symptomatic candidemia resulting from a large right atrial abscess obstructing the tricuspid valve; despite antifungal therapy, urgent surgical resection was required.